Utilização de geotêxteis como reforço de aterros sobre solos moles - Palmeira, Ennio Marques (1981)
This thesis presents a study on geotextile application for stabilizing low embankment roads constructed on weak foundation soils. A bibliography review on the main characteristics of some commercially available geotextiles, their physical and mechanical properties, usual manufacturing process and standard geotextile testing methods is presented. A review on geotextile application as reinforcement under the base of low embankment road is also made. A case history is presented on the construction of an instrumented field trial to evaluate geotextile efficiency as reinforcement under the base of an access road on soft ground. The field trial was carried out along the access road for the construction of a second large trial embankment on vertical drains. This experimental program was a part of a large research program sponsored by the Highway Research Institute (Brazil). Six text sections, in which geotextile type and installation method varied, were constructed. Measurements were compared with a section with no reinforcement and also compared with theorectical predictions. Measured geotextile performance, expressed in percent reduction in volume of fill material consumption, seems to vary between 9.6% to 22.6%, depending on the way the geotextile was laterally fixed. An economic evaluation considering fill material and fabric cost at test site, has shown that such a geotextile application would note be economically advantageous unless fill material savings were in excess 26% in volume.